Meningkatkan Kemampuan Bahasa Arab Siswa dalam Program Magang di MTs Nurul Islam Sekarbela - Khairatun Nabiila; Lathiifah Ratu Dewi Mienotie; M. Syauqi Mahfuzh; Nabila Hafizoh Humairoh; Nur Aulia Ulfaturrahmi; Nasarudin Nasarudin (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
The purpose of this study is to investigate the improvement of students' Arabic language skills through an internship program. The methodology used in this study is a quantitative approach to investigate the various teaching methods used during the internship program and their impact on students' Arabic language skills. We collected numerical data to assess the improvement of Arabic language skills. Pre and post-tests are used to measure progress before and after the internship program. The instruments used include Arabic language tests, questionnaires, and language skills assessment scales. The study used the Likert scale to assess participants' perceptions of the internship program In addition, the mastery of vocabulary and the teaching methods used also play an important role in improving students' Arabic language skills. This research is expected to contribute to the development of more effective Arabic teaching methods.